Empirical Evidence of Recurring International Compensation Problems - Harvey, Michael (Journal of International Business Studies, 1993)
The expansion of international business necessitates an increased number of employees based in foreign markets. These expatriates, nationals and third-country nationals represent unique and complex compensation problems. This article addresses five of the recurring compensation problems reported by members of the Society for Human Resource Management International (SHRMI) in a recent survey.